Prevention not cure: a review of methods to avoid sea lice infestations in salmon aquaculture. (24th June 2020) - Barrett, Luke T.; Oppedal, Frode; Robinson, Nick; Dempster, Tim
Abstract: The Atlantic salmon aquaculture industry still struggles with ectoparasitic sea lice despite decades of research and development invested into louse removal methods. In contrast, methods to prevent infestations before they occur have received relatively little research effort, yet may offer key benefits over treatment‐focused methods. Here, we summarise the range of potential and existing preventative methods, conduct a meta‐analysis of studies trialling the efficacy of existing preventative methods and discuss the rationale for a shift to the prevention‐focused louse management paradigm. Barrier technologies that minimise host–parasite encounter rates provide the greatest protection against lice, with a weighted median 76% reduction in infestation density in cages with plankton mesh 'snorkels' or 'skirts', and up to a 100% reduction for fully enclosed cages. Other methods such as geographic spatiotemporal management, manipulation of swimming depth, functional feeds, repellents and host cue masking can drive smaller reductions that may be additive when used in combination with barrier technologies. Finally, ongoing development of louse‐resistant salmon lineages may lead to long‐term improvements if genetic gain is maintained, while the development of an effective vaccine remains a key target. Preventative methods emphasise host resistance traits while simultaneously reducing host–parasite encounters. Effective implementation has the potential to dramatically reduce the need for delousing and thus improve fish welfare, productivity and sustainability in louse‐prone salmon farming regions.